Port-site metastasis in laparoscopic gynecological oncology surgery: An overview - Vahan Manvelyan; Veerapol Khemarangsan; Kuan-Gen Huang; Aizura-Syafinaz Adlan; Chyi-Long Lee (Wolters Kluwer Medknow Publications, 2016)
Despite the low frequency, port-site metastases are associated with poor outcomes in patients and account for significant patient morbidity. They remain a challenging complication of laparoscopic procedures for gynecologic malignancies. A comprehensive, systematic search for published studies was conducted using the PubMed databases. Various mechanisms of port-site metastases are addressed in the relevant literature. The review of the articles points out that in the development of port-site metastases, the major role is played by biologically aggressive diseases, tumor manipulation, wound contamination, and surgery-related factors. The advantages of laparoscopic oncologic surgery are unquestionable. Further investigations of the mechanisms of port-site metastasis would contribute to the prevention of this insidious pathology.